2008
DOI: 10.1089/apc.2006.0216
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of HIV Antiretroviral Therapy Adherence Programs and Impact on Health Care Utilization

Abstract: From a trial comparing interventions to improve adherence to antiretroviral therapy-directly administered antiretroviral therapy (DAART) or an intensive adherence case management (IACM)-to standard of care (SOC), for HIV-infected participants at public HIV clinics in Los Angeles County, California, we examined the cost of adherence programs and associated health care utilization. We assessed differences between DAART, IACM, and SOC in the rate of hospitalizations, hospital days, and outpatient and emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Prior studies of marginalized HIV-infected samples found that participants overestimated outpatient visits and medication adherence, [63][64][65] so rates of treatment utilization in this study may have been even lower than reported. 64,66,67 Future studies might consider multiple assessment methods, including medical record review and Medication Event Monitoring System, and lower adherence thresholds to account for improvements in ART regimens. 12,64,65 Nevertheless, self-reported adherence to ART has been found to predict virologic failure, 68 and it was predictive of immune functioning in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of marginalized HIV-infected samples found that participants overestimated outpatient visits and medication adherence, [63][64][65] so rates of treatment utilization in this study may have been even lower than reported. 64,66,67 Future studies might consider multiple assessment methods, including medical record review and Medication Event Monitoring System, and lower adherence thresholds to account for improvements in ART regimens. 12,64,65 Nevertheless, self-reported adherence to ART has been found to predict virologic failure, 68 and it was predictive of immune functioning in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that HIV case management can improve treatment utilization, including more outpatient visits and fewer hospital days, with lower overall health care costs. 64,66,67 Thus, many HIV-positive adults with CSA might benefit from case management or other interventions to help address psychosocial problems that interfere with optimal treatment utilization.…”
Section: Discussionmentioning
confidence: 99%
“…This is less than some programs (e.g., intensive individual-based) 29 but more than others (e.g., pillbox organizers). 30 The incentive provided to PDI participants ($30 per week) is relatively high, and comprises three quarters of the total program cost; it is feasible that this could be reduced without compromising participation.…”
Section: Peer Intervention For Antiretroviral Adherencementioning
confidence: 92%
“…Unit costs for HICs ranged between US$212 and 28,884, for UMICs between US$8 and 1806, and for LICs the unit cost was US$17,575 (TABLE 7) . Cost-effectiveness analysis of some of these services was performed in HICs and LICs and results were US$14,802 and US$1294-2000, respectively Home-based care 204 [80] 4 [76] Mobile testing 24-64 [34] Door-to-door counseling 15-24 [35] Household member HCT 37-39 [53,75] Rapid testing in transgender community 650-693 [86] Peer referral for MSM 392 [65] Per HIV-positive client tested 428-515 [34] Per client notifi ed of serostatus [77] 217-647 [34] Person notifi ed of new diagnosis 4013-18,740 [52] Transgender community 3817-8874 [86] Newly infected MSM 10,165-13,439 [66] Per person confi rmed with HIV diagnosis…”
mentioning
confidence: 99%